2014
DOI: 10.1002/xrs.2567
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray fluorescence analysis on a group of coins from the ancient roman city of Tridentum (Trento, Italy)

Abstract: A group of 83 coins, found in the archeological excavations of the ancient Roman city of Tridentum (Trento, Italy), was studied for the determination of their composition, finalized to their classification and cataloging.The coins, mainly made of copper-based alloys, were minted between the republican period (II century BC) and the last decades of the western empire (V century AD).The X-Ray Fluorescence archaeometric analysis has allowed a revision of the typological classification of the coins through the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Nowadays, the most common techniques applied to investigate ancient alloys are Scanning Electron Microscope 6,26,27 and X-Ray Fluorescence 22,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the most common techniques applied to investigate ancient alloys are Scanning Electron Microscope 6,26,27 and X-Ray Fluorescence 22,28 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, XRF spectrometry has been used for the analysis of several numismatic collections. 38 The technique is nondestructive, fast, and works very well on archeological metal alloys. In particular, for the analysis of gold alloys, the lack of surface patina is a condition particularly favorable for the application of the XRF technique, 9 which is very sensitive to the presence of surface corrosion.…”
Section: Experimental Setup and Strategymentioning
confidence: 99%
“…For this reason, a semi-quantitative significance is often assigned to portable X-ray fluorescence (pXRF) surface analyses [18]. Several authors have tried to use the pXRF technique for the chemical analysis of the alloy composition, in part because it consists of portable instrument that can be easily transported into the museums where ancient monetary collections are kept [19][20][21][22][23]. Nevertheless, recent studies have shown that the chemical composition of metals with patinas up to 25 µm thick can be satisfactorily investigated with pXRF instrumentation [24].…”
Section: Introductionmentioning
confidence: 99%